A Tale of Two Sites: Cellphones, participatory video and indigeneity in community-based research - Schwab-Cartas, Joshua; Mitchell, Claudia (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
This polyvocal text is both a narrative and a dialogue between two scholar-activist researchers working in rural communities in distinct parts of the world — South Africa and Southern Mexico — sharing their experiences of using cellular phone and camcorders, while also exploring the potential sustainability of these technologies in the context of rural communities engaging with participatory video projects. These communities are not only playing an increasingly salient role as the mediators of this technology, but through their practices they are drawing much needed attention to the ways in which the researcher — participant dynamic in participatory video practices can be transformed into a more autonomous and participant-led set of practices. The article considers the ways these media forms carry the potential to imagine and honour different worldviews.